Legitimasi Yuridis Putusan Hakim Tentang Pernikahan Dalam Masa Syibhul Iddah: Analisis Perkara Nomor: 274/Pdt.P/2024/PA.Wsb - Nur Febriyanti, Salsabila; Hari Widiyanto; Waluyo Sudarmaji (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Divorce in Indonesian law and Islamic law raises issues concerning the iddah period and syibhul iddah, which often create tension between normative legal provisions, the protection of women’s rights, and social realities in the Religious Courts. Judicial decisions permitting former husbands to remarry during the syibhul iddah period, such as in Case No. 274/Pdt.P/2024/PA.Wsb, highlight the importance of examining the legal basis, judicial reasoning, and their conformity with Islamic legal principles and positive law. This study aims to analyze the legal foundations and the use of judicial discretion in granting permission to marry during syibhul iddah, assess its conformity with maqāṣid al-sharī‘ah and positive law, and examine its contribution to legal certainty, public benefit, and the development of contemporary Islamic family law. This research employs a qualitative library research method using a document study approach. The findings indicate that the approval of marriage permission in this case has a strong basis in both positive law and shar‘ī principles, as there is no normative prohibition for men to marry during the syibhul iddah period. Moreover, the decision aligns with maqāṣid al-sharī‘ah by safeguarding nasab, honor, religion, and public welfare